Business process re-engineering in a digital world-consultancy project - Essop, Zubair (My University, 2017)
The purpose of this consultancy project is to evaluate the business to business (B2B) customer management process at a company (anonymous) to identify opportunities for business process re-engineering (BPR). Introducing BPR should ultimately lead to improved efficiency, whilst reducing costs and is intended to positively contribute towards the company’s trading profit being a strategic objective of the organisation. In the face of a rapidly changing environment where local and global competition is intensifying, organisations need to sustain competitive advantage. This can be achieved through implementation of new processes which drive efficient operations management and it can therefore continue to deliver high-quality services, with excellent performance levels, at a low cost. My approach to this consultancy project will entail the following approach:  an understanding of the business problem  researching literature to gain further insight and knowledge on the subject  collection and analysing data related to the business problem  assessing the current process to understand the challenges  noting down the shortcomings of each process  redesigning the process  performing a cost benefit analysis of the solution  discussing an implementation plan Problem Definition Research Collect and Analyse Data Assess Current Process Identifiy Shortcomings Redesign Process Business Case Implementation Plan 8  deployment of the new process, monitoring and benefits realisation follows, but are out of scope for this exercise
MBA
Keywords: Reengineering (Management) -- South Africa. Success in business -- South Africa.